A precarização do trabalho docente nas escolas estaduais de Marechal Cândido Rondon/PR: um estudo sobre os professores PSS - Martins, Jéssica Carolina de Souza (2013)
The study on the casualization of teaching in the State Public Schools, under the guidance of Prof. Dr. José Luiz Zanella Program Graduate Geography Strictu Sensu, MSc level, the State University of West Paraná - Campus Francisco Beltran-PR, aimed to analyze the conditions of teachers' work, in particular teachers PSS , referred to the Public Schools controlled by the State Government of Paraná, in the period 2008-2012, with the cutout area of study, the State Schools of Rondon. The research aims to demonstrate, based on historical elements, as it is possible to perform a reading of the precariousness of work faculty, linking it to changes in society over the centuries and especially when it refers to the world of work, using the reference classical theory, which allows from the historical and dialectical materialism to understand the current circumstances that, in order to understand the process of casualization of labor relations, and in particular the teaching office, closely articulated with the school public. This sense, research tends to demonstrate teaching, nowadays, as susceptible to instability and alienation of the worker.